If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 6 + 6x = 76 Reorder the terms: 6 + X + 6x = 76 Solving 6 + X + 6x = 76 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + X + -6 + 6x = 76 + -6 Reorder the terms: 6 + -6 + X + 6x = 76 + -6 Combine like terms: 6 + -6 = 0 0 + X + 6x = 76 + -6 X + 6x = 76 + -6 Combine like terms: 76 + -6 = 70 X + 6x = 70 Add '-6x' to each side of the equation. X + 6x + -6x = 70 + -6x Combine like terms: 6x + -6x = 0 X + 0 = 70 + -6x X = 70 + -6x Simplifying X = 70 + -6x
| .03x-.15=.09 | | -6+88= | | 13x-42=0 | | 3x^2-2xs-8=0 | | M+0.36=9.75 | | 3n-4=29 | | F(x)=4x^2-16x+6 | | (X^2-14X-98)=0 | | 6+x+3x=-2 | | 6n+5=-151 | | 3y+y=2y-6 | | 2x+3x^2-22=0 | | -4/7x-4=12 | | 7a+4=102 | | 2x=3x^2-22 | | 21/14=7/4 | | 264+26= | | 7-5x=4x-101 | | 8-3x+3x= | | 5-2x=3x-4 | | -72=4(5k-3) | | 3.2(d)= | | 3x-5=8x-4 | | 12ab+(-12ab)= | | .5x+1.2=2.7 | | X+3=7x-51 | | x+163=38+2x+125 | | -2(3x-9)+6=-6x+24 | | -25-6x=10-5x | | 30x^2-87x+30=0 | | 30x^2-87x-30=0 | | -3(-5x+1)=57 |